Recomendação de nitrogênio e potássio para trigo, milho e soja sob sistema plantio direto no Paraguai - Wendling, Ademir (2005)
More than 50% of the cultivated areas in the Southern Brazil and more than 60% of the cultivable area in Paraguay adopted the no-tillage system. This system went through several improvements, but there are still doubts about the fertilizing recommendation. Nitrogen (N) and potassium (P) are the nutrients absorbed in largest quantities and their deficiencies affect crop productivity. In this sense, the purpose of this study was to develop a nitrogen and potassium fertilizer recommendation system suitable for wheat, corn and soybean under no-tillage system in Paraguay. Seven field experiments were conducted in four Paraguayan Departments, which include the main grain production regions. Soils in these regions are mainly Oxisols , Inceptisols and Ultisols. Experimental design was random blocks with three replications. Treatments consisted of five rates of N for wheat (0, 30, 60, 90 e 120 kg ha-1 of N), five for corn (0, 60, 120, 180 e 240 kg ha-1 of N), and five rates of K (0, 25, 50, 75 e 100 kg ha-1 of K2O) for corn, wheat and soybean. Those nutrients there are not included in the study were properly supplied. For N, curves of these crops were made and maximum technical and economical efficiencies were calculated, as well as lavels of fertilizers recommended for corn and wheat under notillage system. For K, the soil critical level was determined, correlating level of K in the soil (determined by the method Mehlich 1) and the plant response (relative productivity). It was also determined lavels of K needed to attain the critical le vel in the soil and also to maintain it after it was reached. For wheat, it is necessary 35 kg ha-1 of N to reach 3100 kg ha-1 of wheat after soybean, and after corn it is necessary 30 kg ha-1 of N for a productivity of 2100 kg ha-1 of wheat. Wheat responds to residual N applied in corn. For a productivity of 6000 kg ha-1 of corn it is necessary 90 kg ha-1 after the wheat with little straw leftover. On the other hand, when there is a large quantity of straw and the no-tillage system is not stabilized, 130 kg ha-1 of N is needed. For a productivity of 8000 kg ha-1 of corn, 120 kg ha-1 of N is necessary in a consolidated no-tillage system. The critical level of K in the soil as determined by the Mehlich 1 method is 74 mg dm-3 for a relative productivity of 90%. To increase one mg dm-3 the level of K in the soil, 5 kg ha-1 of K2O is needed. At levels above 150 mg dm-3 plants do not respond to K application and only starting rates are recommended for wheat, corn and soybean crops.